5PSQ-092 Analysis of off-label uses of inhalers in hospitalised patients. (2nd March 2018) - Villamañán, E; Freire, M; Sobrino, C; Jiménez, I; Lara, C; Ruano, M; Pérez, E; Jiménez, C; Rossignoli, A; Herrero, A
Abstract : Background: The high prevalence of respiratory diseases leads to high consumption of inhaled bronchodilators (IBs) not always appropriately indicated. It is important for patients and for the healthcare systems that a proper indication and use not only achieves greater efficacy and adherence to the treatment, but also because of the high economic impact of these medications. Purpose: To analyse indications for which IBs are used in hospitals and how many of them were off-label. Medical specialties involved in the prescriptions of IBs and whether they were initiated at admission or in primary care were also evaluated. Material and methods: Descriptive, observational, cross-sectional study in a tertiary hospital of 1350 beds in Spain. Pharmacotherapy including IBs that are prescribed to inpatients in our centre are registered in an electronic prescription program (FarmaTools ® version 5.0). Primary outcome: number of hospitalised patients treated with IBs whose indication is considered off-label. Authorised indications by the European Medicines Agency were considered appropriate. Results: The pharmacotherapy of 555 admitted patients was analysed, 104 patients (18.7%) were prescribed IBs (63.6% males, mean age 70±14.2). 33 of them (31.7%; 95% CI: 22.9 to 41.6) were used for off-label indications: 54.5% for non-respiratory diseases, mainly heart diseases (46.1%) and 45.4% for respiratory diseases without bronchoconstriction (respiratory failure in 24.2% and respiratory infections in 15.1%). The remaining 67 (64.4%) were prescribed for approved indications (85.1% COPD and 14.9% asthma). Forty-one (39.4%) treatments with IBs were initiated at admission and 63 (60.6%) in primary care. As for the medical specialties responsible for the inhaler first prescription, 29 (46%) of them were initially prescribed by general practitioners and 34 (54%) by pneumologists. Conclusion: A high proportion of admitted patients are prescribed BIs, many of them used for off-label indications for which they have not proved effective. Physicians, when prescribing IBs to patients with respiratory distress, should assess comprehensively whether indication is adequate or not taking into account that they are useful if it is associated with bronchoconstriction. On the other hand, hospital pharmacists when reviewing treatments at admission have a good opportunity for deprescribing IBs inappropriately initiated in primary care in order to avoid inefficiency and potential adverse effects. References and/or Acknowledgements: Pharmacy and pneumology ward staff. No conflict of interest